Telemedicine Across the Globe-Position Paper From the COVID-19 Pandemic Health System Resilience PROGRAM (REPROGRAM) International Consortium (Part 1) - Bhaskar, Sonu; Bradley, Sian; Chattu, Vijay Kumar; Adisesh, Anil; Nurtazina, Alma; Kyrykbayeva, Saltanat; Sakhamuri, Sateesh; Yaya, Sanni; Sunil, Thankam; Thomas, Pravin; Mucci, Viviana; Moguilner, Sebastian; et al. (Frontiers in Public Health, 2020)
Coronavirus disease 2019 (COVID-19) has accelerated the adoption of telemedicine globally. The current consortium critically examines the telemedicine frameworks, identifies gaps in its implementation and investigates the changes in telemedicine framework/s during COVID-19 across the globe. Streamlining of global public health preparedness framework that is interoperable and allow for collaboration and sharing of resources, in which telemedicine is an integral part of the public health response during outbreaks such as COVID-19, should be pursued. With adequate reinforcement, telemedicine has the potential to act as the “safety-net” of our public health response to an outbreak. Our focus on telemedicine must shift to the developing and under-developing nations, which carry a disproportionate burden of vulnerable communities who are at risk due to COVID-19.